2004
DOI: 10.1111/j.1600-0528.2004.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

A standardized photographic method for evaluating enamel opacities including fluorosis

Abstract: The photographic method was mostly robust and reproducible when used by epidemiologists from seven European study sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 12 publications
1
66
0
3
Order By: Relevance
“…Furthermore, there is conflicting evidence regarding the accuracy of using 3DI orthodontic casts in the assessment of occlusion [9,10]. The use of two-dimensional digital images (2DI) to simulate a patients' dentition is emerging as a potential alternative to clinical assessment (chair-side assessments) and to other replicas of patients' dentitions [11,12]. 2DI is a quick and durable way of obtaining records of patients' dentition, and readily transmitted for referrals, consultations, presentations, and use in multicenter studies [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is conflicting evidence regarding the accuracy of using 3DI orthodontic casts in the assessment of occlusion [9,10]. The use of two-dimensional digital images (2DI) to simulate a patients' dentition is emerging as a potential alternative to clinical assessment (chair-side assessments) and to other replicas of patients' dentitions [11,12]. 2DI is a quick and durable way of obtaining records of patients' dentition, and readily transmitted for referrals, consultations, presentations, and use in multicenter studies [13].…”
Section: Introductionmentioning
confidence: 99%
“…Only two others have been conducted thus far: one American and one carried out in seven European countries. Despite the various published manuscripts found in the literature, only the first of these studies has published data on fluorosis in the permanent dentition and its association to fluoride intake [Levy et al, 1998[Levy et al, , 2000[Levy et al, , 2001Warren et al, 2002;Levy, 2003;Cochran et al, 2004a-d, O'Mullane et al, 2004avan Loveren et al, 2004;Whelton et al, 2004;Franzman et al, 2006;Hong et al, 2006a, b]. This paper presents a prospective study on the association of fluoride intake by children and the occurrence of dental fluorosis in their permanent central incisors and first molars after a 6-year interval.…”
mentioning
confidence: 99%
“…[8][9][10] Results of other studies have also suggested that although photographs are a suitable tool to assess WSL, they have tended to both under-and overscore when compared to clinical photographs. [11][12] In conclusion, certain methodological issues of the current study warrant caution. However, its results add to the body of evidence to support the use of F varnish as a professional preventive therapy for patients undergoing orthodontic treatment.…”
Section: Commentary and Analysismentioning
confidence: 77%